Modulation of the Gut Microbiota by Olive Oil Phenolic Compounds: Implications for Lipid Metabolism, Immune System, and Obesity - Farràs, Marta (Nutrients, 2020)
There is extensive information of the beneficial effects of virgin olive oil (VOO), especially on cardiovascular diseases. Some VOO healthy properties have been attributed to their phenolic-compounds (PCs). The aim of this review is to present updated data on the effects of olive oil (OO) PCs on the gut microbiota, lipid metabolism, immune system, and obesity, as well as on the crosstalk among them. We summarize experiments and clinical trials which assessed the specific effects of the olive oil phenolic-compounds (OOPCs) without the synergy with OO-fats. Several studies have demonstrated that OOPC consumption increases Bacteroidetes and/or reduces the Firmicutes/Bacteroidetes ratio, which have both been related to atheroprotection. OOPCs also increase certain beneficial bacteria and gut-bacteria diversity which can be therapeutic for lipid-immune disorders and obesity. Furthermore, some of the mechanisms implicated in the crosstalk between OOPCs and these disorders include antimicrobial-activity, cholesterol microbial metabolism, and metabolites produced by bacteria. Specifically, OOPCs modulate short-chain fatty-acids produced by gut-microbiota, which can affect cholesterol metabolism and the immune system, and may play a role in weight gain through promoting satiety. Since data in humans are scarce, there is a necessity for more clinical trials designed to assess the specific role of the OOPCs in this crosstalk.